Molecular detection, quantification and characterization of extended-spectrum β-lactamase (ESBL)- and AmpC-encoding genes in a cucumber agroecosystem - Korsten, Lise (University of Pretoria, 2021)
Dissertation (MSc (Biotechnology))--University of Pretoria, 2021.